Thermal insulation material and high-strength EPS (Expandable Polystyrene) foam box prepared from thermal insulation material

By using graphene-modified EPS particles and a specific raw material ratio, the shortcomings of existing insulation materials and EPS foam boxes in terms of strength, waterproofness, and preparation technology are solved, achieving high strength, excellent waterproof performance, and consistent insulation effects. insulation materials and foam boxes.

CN119307051APending Publication Date: 2025-01-14TAICANG DAZHONG PACKAGING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411289103.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing insulation materials and EPS foam boxes have obvious defects in strength, waterproofness, modification methods and preparation processes, which leads to their easy breakage during transportation and use, limited waterproof performance, short service life, and difficult preparation process. Precise control.

Method used

Graphene-modified EPS particles are used, and through specific raw material ratios and preparation processes, including suspension polymerization and polymerization foaming, insulation materials with high strength and excellent waterproof properties are prepared. The material also incorporates ingredients such as styrene-acrylonitrile copolymer, polyurethane prepolymer, redispersible latex powder, hydroxypropyl methylcellulose ether and polypropylene fiber to improve the overall performance of the material.

Benefits of technology

It significantly improves the strength and toughness of the insulation material, improves the waterproof performance, extends the service life, and ensures the consistency of the foam box in terms of insulation effect, dimensional stability and surface flatness, meeting the demand for high-quality insulation products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307051A_ABST
    Figure CN119307051A_ABST
Patent Text Reader

Abstract

According to the thermal insulation material and the high-strength EPS foam box prepared from the thermal insulation material, the thermal insulation material is prepared from various raw materials including modified EPS particles, styrene-acrylonitrile copolymer, polyurethane prepolymer and the like according to a specific ratio through a specific process. Wherein the modified EPS particles are modified by graphene, so that the strength and thermal insulation performance of the thermal insulation material are remarkably improved. The foam box has excellent thermal insulation, high strength and waterproof performance, and is suitable for various occasions needing thermal insulation protection. The preparation method comprises the steps of premixing, foaming agent adding, mold preparation, mixture injection, foaming, curing, demolding and the like, the process is simple, operation is easy, and the prepared EPS foam box is stable in quality and excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal insulation materials, and specifically discloses a thermal insulation material and a high-strength EPS foam box prepared thereby. Background Art

[0002] In the existing technical field, thermal insulation materials and their products, such as EPS foam boxes, play a vital role in many industries, especially in the fields of cold chain logistics, building insulation, packaging protection, etc. However, these traditional thermal insulation materials and foam boxes still have several significant defects in performance and application, which need to be improved urgently. First, although traditional EPS (polystyrene) foam materials have good thermal insulation performance, their strength and toughness are relatively insufficient, and they are prone to damage during transportation or use, thus affecting the thermal insulation effect and the integrity of the product. This shortcoming is particularly prominent in application scenarios that need to withstand large external forces or complex environmental conditions. Secondly, the waterproof performance of traditional EPS foam materials is limited. Once they encounter water or humid environments, they are easy to absorb water, resulting in a decrease in thermal insulation performance, and even mildew, which seriously shortens the service life. At the same time, this also increases the risk of using the material in a humid environment and limits its scope of application. Furthermore, in the preparation process of existing thermal insulation materials, there is often a lack of effective modification methods to significantly improve their comprehensive performance. For example, although some studies have tried to improve the performance of EPS foam by adding different types of additives, the effect is not significant and is often accompanied by a substantial increase in costs. In addition, the preparation process of traditional EPS foam boxes is relatively simple, but it is often difficult to accurately control the foaming process and the performance of the final product. This leads to large differences in the thermal insulation effect, dimensional stability, surface flatness, etc. of the foam boxes, making it difficult to meet the high-precision and high-quality application requirements.

[0003] In summary, existing thermal insulation materials and EPS foam boxes have obvious defects in strength, waterproofness, modification methods and preparation processes. Summary of the invention

[0004] Based on the deficiencies in the prior art, the present invention discloses a thermal insulation material and a high-strength EPS foam box prepared thereby.

[0005] The present invention includes the following technical solutions:

[0006] A thermal insulation material, calculated by weight, is made of the following raw materials:

[0007]

[0008] The modified EPS particles are graphene-modified EPS particles.

[0009] Furthermore, in the above-mentioned thermal insulation material, the modified EPS particles are prepared by the following steps:

[0010] S1: Sodium borohydride, graphene flakes and alkylbenzene sulfonic acid are mixed in a mass ratio of 10:1-2:5-8 and then treated in an ice bath to obtain material A;

[0011] S2: Add 0.02-0.1 times the mass of hydrazine to material A and heat to 50-60°C for 20-40 minutes to obtain material B;

[0012] S3 material B is mixed with styrene monomer in an amount of 0.1-0.5 times the mass of material B, and polymerized into polystyrene particles by suspension polymerization method, the reaction temperature is 80-90°C; wherein the initiator is azobisisobutyronitrile, and the amount used is 0.01-0.03 times the mass of styrene monomer; the suspending agent is polyvinyl alcohol, and the amount used is 0.1-0.3 times the mass of styrene monomer; the stirring speed is 500-750rpm, and the reaction time is 60-120min, to obtain material C;

[0013] S4: material C is polymerized and foamed with n-pentane having a mass of 0.5-0.8 times the mass of material C at room temperature and pressure to obtain graphene-modified polystyrene foam particles;

[0014] S5: heating and pressurizing the modified expanded particles to prepare particles, preferably at a temperature of 105-110° C. and a pressure of 1.5-2 atmospheres.

[0015] Furthermore, in the above-mentioned thermal insulation material, the heat deformation temperature of the polystyrene-acrylonitrile copolymer is 105-115°C.

[0016] Furthermore, in the above-mentioned thermal insulation material, the polyurethane prepolymer is of polyether type.

[0017] Furthermore, in the above-mentioned thermal insulation material, the average particle size of the redispersible latex powder is 50-100 μm.

[0018] Furthermore, in the above-mentioned thermal insulation material, the viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s.

[0019] Furthermore, in the above-mentioned thermal insulation material, the equivalent diameter of the polypropylene fiber is 28-70 μm, and the length is 3-200 mm.

[0020] Furthermore, in the above-mentioned thermal insulation material, the organic silicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

[0021] The invention also discloses a high-strength EPS foam box, which is made of the above-mentioned thermal insulation material.

[0022] The present invention also discloses a method for preparing the high-strength EPS foam box, which comprises the following steps:

[0023] 1) Premixing: In a mixer, preliminarily mix the modified EPS particles, styrene-acrylonitrile copolymer, polyurethane prepolymer, redispersible latex powder, hydroxypropyl methyl cellulose ether and polypropylene fiber at a temperature of 50-80° C. and a stirring speed of 300-600 rpm to obtain a mixture A;

[0024] 2) Adding the foaming agent: keeping the temperature and stirring speed unchanged, gradually adding the foaming agent after premixing, and continuing to mix until the foaming agent is evenly distributed in the mixture A, to obtain a mixture B;

[0025] 3) Mold preparation: prepare a mold that matches the size of the EPS foam box, ensure that the mold surface is smooth and free of defects, and apply a layer of release agent to facilitate subsequent demolding;

[0026] 4) Injecting the mixture: Inject the mixture B into the mold, filling it evenly to avoid bubbles or voids;

[0027] 5) Foaming: Place the mold in a foaming machine or heating equipment, control the temperature to 105-115°C, the pressure to 2-3 atmospheres, and the time to 10-20 minutes;

[0028] 6) Curing: After foaming is completed, let the foam cool and solidify naturally in the mold;

[0029] 7) Demolding: After curing is completed, the foam box is taken out of the mold to obtain a high-strength EPS foam box.

[0030] Compared with the prior art, the present invention has the following outstanding beneficial effects:

[0031] The present invention discloses a thermal insulation material and a high-strength EPS foam box prepared therefrom. First, by adopting graphene-modified EPS particles, the strength and toughness of the thermal insulation material are significantly improved, so that it can withstand greater external forces without being easily damaged, thereby extending the service life. Secondly, the addition of an organosilicon waterproofing agent effectively improves the waterproof performance of the material, and it can maintain an excellent thermal insulation effect even in a humid environment, avoiding the performance degradation and mildew problems caused by water absorption. In addition, the thermal insulation material also ensures the excellent comprehensive performance of the final product by precisely controlling the raw material ratio and preparation process. The high heat deformation temperature of the styrene-acrylonitrile copolymer enhances the thermal stability of the material, and the introduction of the polyurethane prepolymer further enhances the thermal insulation effect. The addition of redispersible latex powder, hydroxypropyl methylcellulose ether and polypropylene fiber enhances the adhesion, flexibility and crack resistance of the material, making the thermal insulation material more sturdy and durable.

[0032] Therefore, the high-strength EPS foam box made of the above-mentioned insulation material of the present invention not only has excellent insulation performance and waterproof performance, but also has higher strength and toughness, and is suitable for use in various complex environmental conditions. Its preparation method is simple and efficient, and can accurately control the foaming process and the performance of the final product, ensuring the consistency of the foam box in terms of insulation effect, dimensional stability and surface flatness, etc., and meeting the market demand for high-quality insulation products. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Comparative test of thermal conductivity (λ) W / (m·K) of thermal insulation materials;

[0034] Figure 2 Comparative test of the compressive strength (Mpa) of thermal insulation materials;

[0035] Figure 3 It is a comparative test of the tensile strength (Mpa) of thermal insulation materials. DETAILED DESCRIPTION

[0036] A thermal insulation material, calculated by weight, is made of the following raw materials:

[0037]

[0038] The modified EPS particles are graphene-modified EPS particles.

[0039] The modified EPS particles are prepared by the following steps:

[0040] S1: Sodium borohydride, graphene flakes and alkylbenzene sulfonic acid are mixed in a mass ratio of 10:1-2:5-8 and then treated in an ice bath to obtain material A;

[0041] S2: Add 0.02-0.1 times the mass of hydrazine to material A and heat to 50-60°C for 20-40 minutes to obtain material B;

[0042] S3 material B is mixed with styrene monomer in an amount of 0.1-0.5 times the mass of material B, and polymerized into polystyrene particles by suspension polymerization method, the reaction temperature is 80-90°C; wherein the initiator is azobisisobutyronitrile, and the amount used is 0.01-0.03 times the mass of styrene monomer; the suspending agent is polyvinyl alcohol, and the amount used is 0.1-0.3 times the mass of styrene monomer; the stirring speed is 500-750rpm, and the reaction time is 60-120min, to obtain material C;

[0043] S4: material C is polymerized and foamed with n-pentane having a mass of 0.5-0.8 times the mass of material C at room temperature and pressure to obtain graphene-modified polystyrene foam particles;

[0044] S5: heating and pressurizing the modified expanded particles to prepare particles, preferably at a temperature of 105-110° C. and a pressure of 1.5-2 atmospheres.

[0045] The heat deformation temperature of the polystyrene-acrylonitrile copolymer is 105-115°C;

[0046] The polyurethane prepolymer is of polyether type;

[0047] The average particle size of the redispersible latex powder is 50-100 μm;

[0048] The viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s;

[0049] The polypropylene fiber has an equivalent diameter of 28-70 μm and a length of 3-200 mm;

[0050] The organosilicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] EPS particles were purchased from Wenan County Yingtong Environmental Protection Technology Co., Ltd. The thermal conductivity of type A foam particles was 0.030 W / (m·K).

[0053] Styrene-acrylonitrile copolymer AS (SAN) was Formosa Chemicals NF2200AR purchased from Dongguan Baojia Plastic Co., Ltd.

[0054] The polyurethane prepolymer was MDI and TDI terminated casting polyether type, cas:103837-45-2, purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd.

[0055] Redispersible latex powder was purchased from Hebei Chaoyan New Material Technology Co., Ltd.

[0056] Hydroxypropyl methylcellulose ether was purchased from Jinzhou Xincheng Cellulose Co., Ltd.

[0057] Polypropylene fiber was purchased from Xinfeng Cellulose Factory, Hanzhuang, Dacheng County.

[0058] The organosilicon waterproofing agent was purchased from Jiangxi Hongshi New Materials Co., Ltd. and had a hydrogen content of 1.6 wt%.

[0059] The foaming agent was purchased from Shanghai Ruiyi Environmental Protection Technology Co., Ltd. under the brand Enasolv fs39.

[0060] Example 1

[0061] A thermal insulation material, calculated by weight, is made of the following raw materials:

[0062]

[0063]

[0064] The modified EPS particles are graphene-modified EPS particles.

[0065] The modified EPS particles are prepared by the following steps:

[0066] S1: Sodium borohydride, graphene flakes and alkylbenzene sulfonic acid are mixed in a mass ratio of 10:1:5 and then treated in an ice bath to obtain material A;

[0067] S2: Add 0.02 times the mass of hydrazine to material A and heat to 50-60°C for 20-40 minutes to obtain material B;

[0068] S3 material B is mixed with styrene monomer of 0.1 times the mass of material B, and polymerized into polystyrene particles by suspension polymerization method, the reaction temperature is 80-90°C; wherein the initiator is azobisisobutyronitrile, the amount of which is 0.01 times the mass of styrene monomer; the suspending agent is polyvinyl alcohol, the amount of which is 0.1 times the mass of styrene monomer; the stirring speed is 500-750rpm, the reaction time is 60-120min, and material C is obtained;

[0069] S4: Material C is polymerized and foamed with n-pentane having a mass 0.5 times the mass of material C at room temperature and pressure to obtain graphene-modified polystyrene foam particles;

[0070] S5: heating and pressurizing the modified expanded particles to prepare particles, preferably at a temperature of 105-110° C. and a pressure of 1.5-2 atmospheres.

[0071] The heat deformation temperature of the polystyrene-acrylonitrile copolymer is 105-115°C;

[0072] The polyurethane prepolymer is of polyether type;

[0073] The average particle size of the redispersible latex powder is 50-100 μm;

[0074] The viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s;

[0075] The polypropylene fiber has an equivalent diameter of 28-70 μm and a length of 3-200 mm;

[0076] The organosilicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

[0077] Example 2

[0078] A thermal insulation material, calculated by weight, is made of the following raw materials:

[0079]

[0080]

[0081] The modified EPS particles are graphene-modified EPS particles.

[0082] The modified EPS particles are prepared by the following steps:

[0083] S1: Sodium borohydride, graphene flakes and alkylbenzene sulfonic acid are mixed in a mass ratio of 10:1.5:6 and then treated in an ice bath to obtain material A;

[0084] S2: Add 0.05 times the mass of hydrazine to material A and heat to 50-60°C for 20-40 minutes to obtain material B;

[0085] S3 material B is mixed with styrene monomer of 0.3 times the mass of material B, and polymerized into polystyrene particles by suspension polymerization method, the reaction temperature is 80-90°C; the initiator is azobisisobutyronitrile, the amount of which is 0.02 times the mass of styrene monomer; the suspending agent is polyvinyl alcohol, the amount of which is 0.2 times the mass of styrene monomer; the stirring speed is 500-750rpm, the reaction time is 60-120min, and material C is obtained;

[0086] S4: Material C is polymerized and foamed with n-pentane (0.65 times the mass of material C) at room temperature and pressure to obtain graphene-modified polystyrene foam particles;

[0087] S5: heating and pressurizing the modified expanded particles to prepare particles, preferably at a temperature of 105-110° C. and a pressure of 1.5-2 atmospheres.

[0088] The heat deformation temperature of the polystyrene-acrylonitrile copolymer is 105-115°C;

[0089] The polyurethane prepolymer is of polyether type;

[0090] The average particle size of the redispersible latex powder is 50-100 μm;

[0091] The viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s;

[0092] The polypropylene fiber has an equivalent diameter of 28-70 μm and a length of 3-200 mm;

[0093] The organosilicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

[0094] Example 3

[0095] A thermal insulation material, calculated by weight, is made of the following raw materials:

[0096]

[0097]

[0098] The modified EPS particles are graphene-modified EPS particles.

[0099] The modified EPS particles are prepared by the following steps:

[0100] S1: Sodium borohydride, graphene flakes and alkylbenzene sulfonic acid are mixed in a mass ratio of 10:2:8 and then treated in an ice bath to obtain material A;

[0101] S2: Add 0.1 times the mass of hydrazine to material A and heat to 50-60°C for 20-40 minutes to obtain material B;

[0102] S3 material B is mixed with styrene monomer of 0.5 times the mass of material B, and polymerized into polystyrene particles by suspension polymerization method, the reaction temperature is 80-90°C; the initiator is azobisisobutyronitrile, the amount of which is 0.03 times the mass of styrene monomer; the suspending agent is polyvinyl alcohol, the amount of which is 0.3 times the mass of styrene monomer; the stirring speed is 500-750rpm, the reaction time is 60-120min, and material C is obtained;

[0103] S4: Material C is polymerized and foamed with n-pentane having a mass 0.8 times the mass of material C at room temperature and pressure to obtain graphene-modified polystyrene foam particles;

[0104] S5: heating and pressurizing the modified expanded particles to prepare particles, preferably at a temperature of 105-110° C. and a pressure of 1.5-2 atmospheres.

[0105] The heat deformation temperature of the polystyrene-acrylonitrile copolymer is 105-115°C;

[0106] The polyurethane prepolymer is of polyether type;

[0107] The average particle size of the redispersible latex powder is 50-100 μm;

[0108] The viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s;

[0109] The polypropylene fiber has an equivalent diameter of 28-70 μm and a length of 3-200 mm;

[0110] The organosilicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

[0111] Comparative Example 1

[0112] A thermal insulation material, calculated by weight, is made of the following raw materials:

[0113]

[0114]

[0115] The heat deformation temperature of the polystyrene-acrylonitrile copolymer is 105-115°C;

[0116] The polyurethane prepolymer is of polyether type;

[0117] The average particle size of the redispersible latex powder is 50-100 μm;

[0118] The viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s;

[0119] The polypropylene fiber has an equivalent diameter of 28-70 μm and a length of 3-200 mm;

[0120] The organosilicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

[0121] Compared with Example 2, this comparative example does not use modified EPS particles, but uses ordinary EPS particles.

[0122] Comparative Example 2

[0123] A thermal insulation material, calculated by weight, is made of the following raw materials:

[0124]

[0125] The modified EPS particles are graphene-modified EPS particles.

[0126] The modified EPS particles are prepared by the following steps:

[0127] S1: Sodium borohydride, graphene flakes and alkylbenzene sulfonic acid are mixed in a mass ratio of 10:1.5:6 and then treated in an ice bath to obtain material A;

[0128] S2: Add 0.05 times the mass of hydrazine to material A and heat to 50-60°C for 20-40 minutes to obtain material B;

[0129] S3 material B is mixed with styrene monomer of 0.3 times the mass of material B, and polymerized into polystyrene particles by suspension polymerization method, the reaction temperature is 80-90°C; the initiator is azobisisobutyronitrile, the amount of which is 0.02 times the mass of styrene monomer; the suspending agent is polyvinyl alcohol, the amount of which is 0.2 times the mass of styrene monomer; the stirring speed is 500-750rpm, the reaction time is 60-120min, and material C is obtained;

[0130] S4: Material C is polymerized and foamed with n-pentane (0.65 times the mass of material C) at room temperature and pressure to obtain graphene-modified polystyrene foam particles;

[0131] S5: heating and pressurizing the modified expanded particles to prepare particles, preferably at a temperature of 105-110° C. and a pressure of 1.5-2 atmospheres.

[0132] The polyurethane prepolymer is of polyether type;

[0133] The average particle size of the redispersible latex powder is 50-100 μm;

[0134] The viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s;

[0135] The polypropylene fiber has an equivalent diameter of 28-70 μm and a length of 3-200 mm;

[0136] The organosilicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

[0137] Compared to Example 2, this comparative example lacks the styrene-acrylonitrile copolymer.

[0138] Test Case

[0139] The thermal insulation materials of Examples 1-3 and Comparative Examples 1-2 were prepared into EPS foam boxes in the following manner:

[0140] 1) Premixing: In a mixer, preliminarily mix (modified) EPS particles, styrene-acrylonitrile copolymer (if any), polyurethane prepolymer, redispersible latex powder, hydroxypropyl methylcellulose ether and polypropylene fiber at a temperature of 65° C. and a stirring speed of 300-600 rpm to obtain a mixture A;

[0141] 2) Adding the foaming agent: keeping the temperature and stirring speed unchanged, gradually adding the foaming agent after premixing, and continuing to mix until the foaming agent is evenly distributed in the mixture A, to obtain a mixture B;

[0142] 3) Mold preparation: prepare a mold that matches the size of the EPS foam box, ensure that the mold surface is smooth and free of defects, and apply a layer of release agent to facilitate subsequent demolding;

[0143] 4) Injecting the mixture: Inject the mixture B into the mold, filling it evenly to avoid bubbles or voids;

[0144] 5) Foaming: Place the mold in a foaming machine or heating equipment, control the temperature to 105-115°C, the pressure to 2-3 atmospheres, and the time to 10-20 minutes;

[0145] 6) Curing: After foaming is completed, let the foam cool and solidify naturally in the mold;

[0146] 7) Demolding: After curing is completed, the foam box is taken out of the mold to obtain a high-strength EPS foam box.

[0147] The material in the above high-strength EPS foam box was sampled and made into a test block of 10 cm x 5 cm x 2 cm (thickness).

[0148] The following tests were conducted to test its thermal insulation performance and mechanical strength. The thermal insulation performance was measured by thermal conductivity (λ) in W / (m·K). The lower the thermal conductivity, the better the thermal insulation performance of the insulation material. The mechanical properties were tested by compressive strength (Mpa) and tensile strength (Mpa). Refer to GB / T 10801.1-2021 "Molded polystyrene foam (EPS) for thermal insulation"

[0149] The results are shown in Table 1 and Figure 1-3 shown.

[0150] Table 1 Thermal insulation material performance test

[0151]

[0152] It can be seen from the data in Table 1 above that the use of modified EPS particles can greatly improve the mechanical strength of the thermal insulation material described in the present invention, so it can be used to prepare high-strength EPS foam boxes. At the same time, its thermal conductivity is also reduced. The above ratio enhances the adhesion, flexibility and crack resistance of the material, making the thermal insulation material more durable.

[0153] The above are only a few preferred embodiments of the present invention, which are described in a more specific and detailed manner, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A thermal insulation material, characterized in that: Calculated by weight, it is made from the following raw materials: Modified EPS particles 100 parts 40-80 parts of styrene-acrylonitrile copolymer Polyurethane prepolymer 15-30 parts Redispersible latex powder 10-15 parts Hydroxypropyl methylcellulose ether 5-10 parts 3-6 parts of polypropylene fiber 10-20 parts of silicone waterproofing agent Foaming agent 15-25 parts The modified EPS particles are graphene-modified EPS particles.

2. A thermal insulation material according to claim 1, characterized in that: The modified EPS particles are prepared by the following steps: S1: Sodium borohydride, graphene flakes and alkylbenzene sulfonic acid are mixed in a mass ratio of 10:1-2:5-8 and then treated in an ice bath to obtain material A; S2: Add 0.02-0.1 times the mass of hydrazine to material A and heat to 50-60°C for 20-40 minutes to obtain material B; S3 material B is mixed with styrene monomer in an amount of 0.1-0.5 times the mass of material B, and polymerized into polystyrene particles by suspension polymerization method, the reaction temperature is 80-90°C; wherein the initiator is azobisisobutyronitrile, and the amount used is 0.01-0.03 times the mass of styrene monomer; the suspending agent is polyvinyl alcohol, and the amount used is 0.1-0.3 times the mass of styrene monomer; the stirring speed is 500-750rpm, and the reaction time is 60-120min, to obtain material C; S4: material C is polymerized and foamed with n-pentane having a mass of 0.5-0.8 times the mass of material C at room temperature and pressure to obtain graphene-modified polystyrene foam particles; S5: heating and pressurizing the modified expanded particles to prepare particles, preferably at a temperature of 105-110° C. and a pressure of 1.5-2 atmospheres.

3. A thermal insulation material according to claim 1, characterized in that: The heat deformation temperature of the polystyrene-acrylonitrile copolymer is 105-115°C.

4. A thermal insulation material according to claim 1, characterized in that: The polyurethane prepolymer is of polyether type.

5. The thermal insulation material according to claim 1, characterized in that: The average particle size of the redispersible latex powder is 50-100 μm.

6. A thermal insulation material according to claim 1, characterized in that: The viscosity of the hydroxypropyl methylcellulose ether is 15mPa.s-30mPa.s.

7. The thermal insulation material according to claim 1, characterized in that: The polypropylene fiber has an equivalent diameter of 28-70 μm and a length of 3-200 mm.

8. The thermal insulation material according to claim 1, characterized in that: The organosilicon waterproofing agent is hydrogen-containing silicone oil HTN-004.

9. A high-strength EPS foam box, characterized in that: The thermal insulation material is prepared from the thermal insulation material according to any one of claims 1 to 8.

10. The method for preparing a high-strength EPS foam box according to claim 9, characterized in that: The following steps are involved: 1) Premixing: In a mixer, preliminarily mix the modified EPS particles, styrene-acrylonitrile copolymer, polyurethane prepolymer, redispersible latex powder, hydroxypropyl methyl cellulose ether and polypropylene fiber at a temperature of 50-80°C and a stirring speed of 300-600 rpm to obtain a mixture A; 2) Adding the foaming agent: Keeping the temperature and stirring speed unchanged, gradually add the foaming agent after premixing, and continue mixing until the foaming agent is evenly distributed in the mixture A to obtain the mixture B; 3) Mold preparation: prepare a mold that matches the size of the EPS foam box, ensure that the mold surface is smooth and free of defects, and apply a layer of release agent to facilitate subsequent demolding; 4) Injection of mixture: Inject mixture B into the mold, filling evenly to avoid bubbles or voids; 5) Foaming: Place the mold in a foaming machine or heating equipment, control the temperature to 105-115°C, the pressure to 2-3 atmospheres, and the time to 10-20 minutes; 6) Curing: After foaming is completed, let the foam cool and solidify naturally in the mold; 7) Demolding: After curing is completed, take the foam box out of the mold to obtain a high-strength EPS foam box.